Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3844/ojbsci.2015.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flowcytometric and Immunocytochemistry Analysis of Stem Cell Surface Markers

Abstract: Flowcytometric analysis is widely used in characterization of stem cells. In areas where flowcytometry is not available, characterization of stem cells can be done using immunocytochemistry. This study aimed to compare the results of flowcytometry against immunocytochemistry for the measurement of CD34, CD73 and CD90 in stem cells. Adipose tissue derived stem cells were analyzed for their CD34, D73 and CD90 simultaneously, using a BD FACSCalibur flowcytometer (BD Biosciences) with 10,000 gated events. The same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have identified the properties of stem cells originating from the umbilical cord (UC-MSCs) (41). The conditioned medium (UC-MSCs) Vascular Endothelial Growth Factor (VEGF) was been detected with Enzyme-Linked Immunosorbent Assay (ELISA) detection method (42).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the properties of stem cells originating from the umbilical cord (UC-MSCs) (41). The conditioned medium (UC-MSCs) Vascular Endothelial Growth Factor (VEGF) was been detected with Enzyme-Linked Immunosorbent Assay (ELISA) detection method (42).…”
Section: Introductionmentioning
confidence: 99%